Suspendre le sens, admettre l’accident : une approche sémiotique de la planification urbaine - Lucile Berthomé (EchoGéo)
Based on a socio-semiotic model, the interaction model conceptualised by Éric Landowski (2006), this article looks at the horizons that could be offered by urban planning thought in the interstices of the plan/non-plan opposition. Using this approach, and in the spirit of Renaudie (2011), Desjardin (2020) and Adam and Comby (2021), we wish to examine the role that urban planning could play in the dynamics of (re)conquering the production of space (Lefebvre, 1974). In this perspective, we will draw on fieldwork (cognitive mapping, semio-discursive analysis, qualitative interviews) carried out on two Bordeaux-based initiatives: the Sentier des Terres Communes, a peri-urban walking trail, and Darwin Écosystème, an urban common.